HUBUNGAN TINGKAT KEMAMPUAN PERAWATAN DIRI DENGAN PERUBAHAN KONSEP DIRI PADA LANSIA DI UPT PELAYANAN SOSIAL LANJUT USIA DAN ANAK BALITA WILAYAH BINJAI MEDAN - Dedi dedi (Jurnal Maternitas Kebidanan, 2019)
Background; Elderly age is the biological systems that undergo changes in the structure and function due to old age. One of service unit that serves the safety of the elderly is UPT of Social Service of Elderly and Early Childhood in Binjai and Medan Regional. Based on the preliminary research of this study was found some old people who experienced changes of the self-care ability with self concept change by 7 men and 28 women. Objectives; This study purpose is to determine the relationship between the level of self-care ability of elderly with changes in self-concept of the elderly in UPT of social Services Elderly Social and Early Children in Binjai and Medan. Material and Method; This study used analytical (explanatory research) with cross sectional approach. The population of this study amounted to 72 people and sample in this study were taken from the population amounted 63 respondents by using purposive sampling techniques. The data used primary data, secondary data, the data tertiary, and the analysis of data was done with univariate and bivariate analysis by using chi-square test. Results;of this study with a statistical test of chi-square that the relationship between the level of self-care ability to change the self-concept of the elderly in UPT. Elderly Care and Early Children in Binjai and Medan p = 0.025 < α = 0.05 is found. Conclusion; of this research is that there is a relationship between the level of self-care ability of elderly with changes in self-concept of the elderly in UPT of Elderly Social Services and Early Childhood area Binjai and Medan. It is suggested to further researchers to do deep research about the treatments themselves with self-concept changes in Social UPT of social service of elderly and Early Childhood in Binjai and Medan regional with another methods.